THE IMPLEMENTATION OF QUR’AN READING AND WRITING METHOD TO ENHANCE MEMORIZATION SKILLS IN ISLAMIC SENIOR HIGH SCHOOLS - Maha, Mhd Zulfadli; Sari, Liza Amelia; Taufik, Muhammad; Mardiana; Syahputra, Abdurrahman (AL-ADABIYAH: Jurnal Pendidikan Agama Islam, 2025)
This study examines the implementation of the Qur’an Reading and Writing Method (QRWM) to enhance students’ memorization skills at MAS Tarbiyah Waladiyah. Using a qualitative descriptive approach, data were collected through observation, interviews, and documentation. The QRWM combines reading, listening, and writing activities that engage visual, auditory, and kinesthetic senses to strengthen memory. Findings show that the method is applied through group recitations, verse-writing exercises, and repetition, with teachers serving as guides, correctors, and motivators. Students who regularly read and write Qur’anic verses achieve faster and more accurate memorization, improved letter recognition, and higher confidence in recitation. The method also cultivates discipline and positive study habits, reinforcing students’ spiritual commitment and the overall quality of Qur’an learning. Penelitian ini mengkaji implementasi Metode Baca Tulis Qur’an (MBTQ) dalam meningkatkan kemampuan hafalan siswa di MAS Tarbiyah Waladiyah. Menggunakan pendekatan kualitatif deskriptif, data dikumpulkan melalui observasi, wawancara, dan dokumentasi. MBTQ menggabungkan kegiatan membaca, mendengar, dan menulis yang melibatkan aspek visual, auditori, dan kinestetik untuk memperkuat daya ingat. Hasil penelitian menunjukkan bahwa metode ini diterapkan melalui kegiatan membaca bersama, latihan menulis ayat, dan pengulangan hafalan, dengan guru berperan sebagai pembimbing dan motivator. Siswa yang rutin membaca dan menulis ayat memiliki hafalan lebih cepat, ketelitian tinggi, serta percaya diri saat menyetorkan hafalan. Metode ini juga menumbuhkan disiplin dan kebiasaan belajar positif yang memperkuat semangat spiritual serta kualitas pembelajaran Al-Qur’an.